Healthcare bricolage in Europe's superdiverse neighbourhoods: a mixed methods study - Jenny Phillimore; Tilman Brand; Hannah Bradby; Beatriz Padilla (BMC, 2019)
Abstract Background Studies of the relationship between diverse populations, healthcare access and health outcomes have been dominated by approaches focusing on ethno-national groups or specific healthcare sectors. Healthcare bricolage conceptualises the processes by which individuals use multiple resources to address health concerns. It is relevant in superdiverse neighbourhoods with complex populations. This paper is original in its application of mixed methods to examine the extent to which, and the reasons why, individuals engage in healthcare bricolage. Methods The study utilized a parallel sequential methodology. Eight superdiverse neighbourhoods were selected, two in each of Bremen, Birmingham, Lisbon and Uppsala. Ethnographic research scoping the nature of each healthcare ecosystem was followed by 160 interviews (20 each neighbourhood) with a maximum variation sample of residents undertaken October 2015 to December 2016. Interviewees were asked to recall a health concern and describe actions taken to attempt resolution. Data was coded with a MAXQDA codebook checked for inter-coder reliability. Interview findings enabled identification of five types of bricolage, the nature of healthcare resources utilised and the factors which influenced residents' tactics. Results were used to design a household survey using new questions and validated epidemiological instruments implemented January to October 2017. Respondents were identified using random address files and interviewed in person or by telephone. Multinomal logistic regressions were used to estimate the effect of changing the values of determinants on the probability of observing an outcome. Results Age, gender, level of education, migration background and extent of functional limitation were associated with bricolage tactics. Individuals demonstrating high levels of agency were more likely than those with low levels to engage in bricolage. Residents with high levels of trust in physicians were less likely to bricolage than those with lower levels of trust. Levels of health literacy showed no significant effects. Conclusions The nature and severity of health concern, trust in physicians and agency shaped residents' bricolage tactics. The concept of bricolage enabled us to make visible the actions and resources utilised around public healthcare systems that would otherwise remain outwith healthcare access research. Actions were frequently undertaken via networks offering insights into healthcare-seeking behaviour.